PENGGUNAAN ZAT PERANGSANG TUMBUH INDOLE BUTYRIC ACID (IBA) PADA STEK KEMBANG KERTAS (Bougainvillea spectabilis) - Suarni, Fransiska; Sukerta, I Made; Ananda, Komang Dean (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Paper flowers are an important element in landscaps used to provide beauty and for other functions. This study aims to: 1). Determine the effect of the use of different Indole Butyric Acid Growth Stiments on the growth of paper flower buds. 2). find out the best concentration of soaking time by using growthinducing substances Indole Butyric Acid which can provide growth for paper flowers. This study used a randomized block design with 6 treatments and could be repeated 4 times so that 24 treatments were obtained. Based on the research results of paper flowers using indole butyric acid growth stimulants can be concluded as follows: with a long immersion study ranging from L1 to L6 ie 2cc / 1lt of water gives a significantly different effect on all treatments. Indole Butyric Acid growth stimulant with 16 hours of immersion (L6) gives very good results on all treatments observed, namely: shoot growth speed (HST), number of shoots (fruit), plant height (cm) number of leaves (strands), leaf area (cm), plant fresh weight (g), root fresh weight (g), oven dry weight of the plant (g), root oven dry weight (g).